2016
DOI: 10.3390/ijms17122115
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Food Restriction during Pregnancy and Lactation Adversely Affect Hepatic Growth and Lipid Metabolism in Three-Week-Old Rat Offspring

Abstract: Maternal malnutrition influences the early development of foetal adaptive changes for survival. We explored the effects of maternal undernutrition during gestation and lactation on hepatic growth and function. Sprague-Dawley rats were fed a normal or a food-restricted (FR) diet during gestation and/or lactation. We performed analyses of covariance (adjusting for the liver weight/body weight ratio) to compare hepatic growth and lipid metabolism among the offspring. Maternal FR during gestation triggered the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Other studies have also demonstrated that IUGR can up-regulate the mRNA expressions of a key transcription factor (Srebp1c) (and its downstream genes), and down-regulate the mRNA expressions of the fatty acid oxidation gene (Ppara), ultimately causing liver lipid metabolism disorder [46]. Lee et al [47] found that IUGR, induced by maternal nutrition restriction, increased the protein expressions of SREBP1 and FASN. These results suggest that the abnormal lipid metabolism in the IUGR piglets was associated with related gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that IUGR can up-regulate the mRNA expressions of a key transcription factor (Srebp1c) (and its downstream genes), and down-regulate the mRNA expressions of the fatty acid oxidation gene (Ppara), ultimately causing liver lipid metabolism disorder [46]. Lee et al [47] found that IUGR, induced by maternal nutrition restriction, increased the protein expressions of SREBP1 and FASN. These results suggest that the abnormal lipid metabolism in the IUGR piglets was associated with related gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of maternal malnutrition during pregnancy have been intensively studied in the lite rature. These studies have proven the metabolic imprinting (or fetal programming) theory, in which the effects caused during the intra-uterine life may induce metabolic disturbances in later periods [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the pups which were breastfed by a malnourished mother had an underdevelopment of multiple bones, such as the tibia, mandible, cranium and femur (Fernandes et al, 2007;Fernandes et al, 2008;Degani Junior et al, 2011;Babinski et al;Luna et al;Confortim et al). Moreover, the maternal malnutrition during the gestational period has also been shown to cause detrimental effects on its offspring (Alippi et al, 2002;Lee et al, 2016;Confortim et al).…”
Section: Discussionmentioning
confidence: 99%